Immunohistochemical Expression of P53 in Renal Cell Carcinoma Subtypes: Ekspresi Imunohistokimia P53 pada Subtipe Karsinoma Sel Ginjal - Taha, Nour D.; Al-Nuaimy, Wahda M.T. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Renal cell carcinoma (RCC) constitutes approximately 2.2% of global cancer incidences and is predominantly of the clear cell subtype. Specific Background: The tumor suppressor gene p53, frequently mutated in over half of human cancers, plays a critical prognostic role in various malignancies. However, Knowledge Gap: its prognostic significance in RCC remains controversial due to inconsistent findings across histopathological parameters and RCC subtypes. Aims: This study aimed to evaluate the immunohistochemical expression of p53 in RCC subtypes and its association with clinicopathological parameters including age, sex, laterality, grade, lymphovascular invasion, and tumor stage. Results: Among 65 RCC cases, p53 expression was observed in only 6.2%, confined exclusively to the clear cell subtype, and predominantly in older males with higher tumor grades (III/IV) and early stages (T1–T2). No statistically significant association was found with any examined parameters. Novelty: The study underscores the rarity of p53 expression in RCC and its subtype-specific occurrence, contrasting with previously reported higher expression rates in other populations. Implications: These findings suggest limited prognostic utility of p53 in RCC within this demographic, and highlight the necessity for standardized methodologies and further multicenter studies to clarify p53’s role.Highlight : P53 expression ditemukan hanya pada 6.2% kasus RCC dan seluruhnya dari subtipe clear cell RCC. Tidak ditemukan hubungan statistik signifikan antara ekspresi P53 dan parameter klinikopatologi seperti usia, jenis kelamin, grade, dan stadium. Ekspresi P53 cenderung lebih banyak muncul pada pasien laki-laki berusia ≥55 tahun, grade tinggi (3–4), dan lokasi ginjal kanan. Keywords : P53, Renal Cell Carcinoma, Immunohistochemistry, Clear Cell RCC, Clinicopathological Correlation